2020
DOI: 10.1111/iju.14294
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical control of the combination of cyclooxygenase‐2 inhibitor and 125I‐brachytherapy for prostate cancer: Post hoc analysis of an open‐label controlled randomized trial

Abstract: Objectives To evaluate the use of cyclooxygenase‐2 inhibitors in patients receiving low‐dose‐rate brachytherapy for prostate cancer. Methods A total of 310 patients with prostate cancer (cT1c‐3aN0M0) who received low‐dose‐rate brachytherapy between May 2010 and July 2013 were enrolled and allocated to one of the two treatment groups (tamsulosin alone 0.2 mg/day for 6 months vs tamsulosin 0.2 mg/day for 6 months plus celecoxib 200 mg/day for 3 months). The primary end‐point was the chronological change in inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…However, it should be noted that the addition of COX-2 inhibitor did not significantly affect the outcomes of randomized clinical trials of non-small cell lung cancer and colon cancer patients 33 , 34 . In PC, several in vivo and in vitro studies showed that anti-cancer effects including improvement of prognosis of COX-2 inhibitors were limited 35 38 . Thus, the chemopreventive and anti-cancer effects of COX-2 inhibitors in PC are still controversial.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the addition of COX-2 inhibitor did not significantly affect the outcomes of randomized clinical trials of non-small cell lung cancer and colon cancer patients 33 , 34 . In PC, several in vivo and in vitro studies showed that anti-cancer effects including improvement of prognosis of COX-2 inhibitors were limited 35 38 . Thus, the chemopreventive and anti-cancer effects of COX-2 inhibitors in PC are still controversial.…”
Section: Resultsmentioning
confidence: 99%
“…However, it should be noted that the addition of COX-2 inhibitor did not signi cantly affect the outcomes of randomized clinical trials of non-small cell lung cancer and colon cancer patients 30,31 . In PC, several in vivo and in vitro studies showed that anti-cancer effects including improvement of prognosis of COX-2 inhibitors were limited [32][33][34][35] . Thus, the chemopreventive and anti-cancer effects of COX-2 inhibitors in PC are still controversial.…”
Section: Discussionmentioning
confidence: 99%